First cytogenetic characterization of the amazon catfish leiarius marmoratus (Gill, 1870) and its hybrid with pseudoplatystoma reticulatum (eigenmann & eigenmann, 1889) - Do Prado, Fernanda Dotti [UNESP]; De Freitas Mourão, Andrea Abrigato; Foresti, Fausto [UNESP]; Senhorini, José Augusto; Porto-Foresti, Fábio [UNESP] (Firenze University Press, 2021)
This study reports the first cytogenetic characterization of the Amazonian catfish Leiarius marmoratus (“jandiá”) and its F1 (first generation) hybrid “cachandiá” with Pseudoplatystoma reticulatum (“cachara”). A diploid number of 56 chromosomes and a single argyrophilic nucleolus organizer region (Ag-NOR) in the short arm of two sub-telocentric chromosomes were observed for both L. marmoratus and P. reticulatum, but with differences in the karyotype formula and the size of the chromosome pair with NORs. The hybrid showed 2n = 56 chromosomes with an intermediate karyotype when compared to the parental species. A single Ag-NOR was maintained in the hybrid but located in two chromosomes with marked differences in size and presenting intraindividual variation in NOR activity (nucleolar dominance). For L. marmoratus and the hybrid, heterochromatic bands were predominately distributed in the terminal, centromeric, and sub-centromeric regions of some chromosomes and 5S rDNA sites located in two distinct sub-telocentric chromosomes, similar to the previously described for P. reticulatum. The data suggested that the hybrid karyotype might be insufficient for a precise discrimination of hybrids, however, Ag-NOR can be used as a chromosome marker to differentiate “cachandiá” from L. marmoratus and P. reticulatum. The current study also provides insights into the chromosomal features of L. marmoratus and contributes with novel cytogenetic information of this native Amazonian catfish included in the Pimelodidae family.
Keywords: Ag-NOR; Cachandiá; Hybrid karyotype; Pimelodidae; Pintado da Amazônia; Yaque